Characterization and optical properties of organic dye films as recording media - Kravets, V.G.; Vinnichenko, K.L.; Prygun, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Efficiency of medium choice for optical information recording is generally determined by homogeneity degree of material on the recording surface and by its structure on the film depth. In this respect pyrosolynes should be the prospective materials. Pyrosolyne dye films were produced on the glass substrates initially remained at room temperature T = 20°C by using different techniques such as vapor deposition and sol-gel modified reactions. One of the precise control methods of material surface physical-chemical state is ellipsometric method. In addition, the optical transmission measurements were carried out for these films within the wavelength range λ = 200-630 nm at two different polarization (p- and s-) of the incident light. It has been shown that the absorption bands near n = 1300 cm⁻¹ are present in ellipsometric parameters spectra in case of the vapor deposited dye film samples. The transmission optical measurements of organic films in the visible range without polarizer showed presence of the absorption bands near λ = 300 and 520 nm. The first absorption band was much more intensive than another. It has been determined that the transmission values measured in polarized in p- and s-directions light differs by 5-8% in comparison with data measured without polarizer.